Penerapan Nilai-Nilai Toleransi Beragama dalam Perspektif Sosiologi Pembangunan Pada Organisasi Mahasiswa (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
This research examines the application of religious tolerance values in student organizations at the University of Jember (UNEJ) from a development sociology perspective. Student organizations, as part of the academic community, play an important role in shaping the attitudes and behaviors of their members. In the context of Indonesian diversity, the application of religious tolerance values among students is very important to support inclusive and sustainable social development. Through a qualitative approach with case studies on several student organizations at UNEJ, this research found that religious tolerance is influenced by factors such as organizational policy, leadership, interaction between members, and the campus social environment.